(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this research paper, we will study some important integral formulas, with the help of which they play a major role in the study of the hypergeometric functions and multivariable Hfunction. In this study we will use these formulas to get the solutions of M-series and general class of polynomials in the form of multivariable H-function. The results proved in general forms and besides of this have been put in a compact from avoiding the occurrence of infinite series and thus making them useful in applications. In this research paper we can obtain new and some modified known results which will brings new ideas and fact in field of hypergeometric and polynomials studies.